A Myo-Inositol-Inducible Expression System for Corynebacterium glutamicum and Its Application - Lu, Nan; Zhang, Chenglin; Zhang, Wenjie; Xu, Haoran; Li, Yuhong; Wei, Minhua; Meng, Jing; Meng, Yan; Wang, Junzhe; Chen, Ning (Frontiers in Bioengineering and Biotechnology, 2021)
Corynebacterium glutamicum is one of important industrial microorganisms for production of amino acids and other value-added compounds. Most expression vector used in C. glutamicum are based on inducible promoter (Ptac or Ptrc) activated by isopropyl-β-D-thiogalactopyranoside (IPTG). However, these vectors seem unsuitable for large-scale industrial production due to the high cost and toxicity of IPTG. Myo-inositol is an ideal inducer because of its non-toxicity and lower price. In this study, a myo-inositol inducible expression vector pMI-4, derived from the expression vector pXMJ19, was constructed. Besides the original chloramphenicol resistance gene cat, multiple cloning site and rrnB terminator, the pMI-4 (6643 bp) contains the iolRq cassette and the myo-inositol inducible promoter PiolT1. The pMI-4 could stably replicate in the C. glutamicum host. Meanwhile, the non-myo-inositol degradation host strain C. glutamicumΔiolGΔoixCΔoixDΔoixE for maintaining the pMI-4 was developed. Overexpression of hemAM and hemL using pMI-4 resulted in significant accumulation of 5-aminolevulinic acid, indicating its potential application in metabolic engineering and industrial fermentation.